IMPLEMENTASI MODEL GUIDED DISCOVERY LEARNING BERBANTUAN AUDIO VISUAL UNTUK MENINGKATKAN MINAT BELAJAR DAN PEMAHAMAN KONSEP SISWA PADA MATERI ELASTISITAS DAN HUKUM HOOKE - Yusrizal Yusrizal; Syahrun Nur; Affrannisah Afrrannisah (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the increase in students' interest in learning and understanding of students' concepts on elasticity and Hooke's law which is taught through the Guide Discovery Learning model assisted by audio-visual media at MAN 4 Aceh Besar. The method in this study is a quasi-experimental design with a pretest posttest control group. This research was conducted on students of class XI MAN 4 Aceh Besar. The sampling technique in this research is purposive sampling. The instruments used are questionnaires and questions. The results of the analysis of the t test (independent sample t test) obtained a significance value of 0.000 <0.05, so it can be concluded that Ha is accepted, meaning that there is a difference in the average learning interest of the experimental class and control class students. The results of the N-gain analysis of the experimental class obtained an average score of 0.68 and the control class obtained an average score of 0.42 in the medium category. The results of the analysis of the t test (independent sample t test) obtained a significance value of 0.000 <0.05, so it can be concluded that Ha is accepted, meaning that there is a difference in the average understanding of the concepts of the experimental class and control class students. The conclusion in this study proves that Guided Discovery Learning assisted by audio-visual media can increase students' interest in learning and understanding of students' concepts on elasticity and Hooke's law